Leveraging Ethnic Group Incidence Variation to Investigate Genetic Susceptibility to Glioma: A Novel Candidate SNP Approach - Jacobs, Daniel I.; Walsh, Kyle M.; Wrensch, Margaret; Wiencke, John; Jenkins, Robert; Houlston, Richard; Bondy, Melissa; Simon, Matthias; Sanson, Marc; Gousias, Konstantinos; Schramm, Johannes; Labussiere, Marianne; et al. (Frontiers in Genetics, 2012)
Objectives: Using a novel candidate SNP approach, we aimed to identify a possible genetic basis for the higher glioma incidence in Whites relative to East Asians and African-Americans. Methods: We hypothesized that genetic regions containing SNPs with extreme differences in allele frequencies across ethnicities are most likely to harbor susceptibility variants. We used International HapMap Project data to identify 3,961 candidate SNPs with the largest allele frequency differences in Whites compared to East Asians and Africans and tested these SNPs for association with glioma risk in a set of White cases and controls. Top SNPs identified in the discovery dataset were tested for association with glioma in five independent replication datasets. Results: No SNP achieved statistical significance in either the discovery or replication datasets after accounting for multiple testing. However, the most strongly associated SNP, rs879471, was found to be in linkage disequilibrium with a previously identified risk SNP, rs6010620, in RTEL1. We estimate rs6010620 to account for a glioma incidence rate ratio of 1.34 for Whites relative to East Asians. Conclusions: We explored genetic susceptibility to glioma using a novel candidate SNP method which may be applicable to other diseases with appropriate epidemiologic patterns.